Pelatihan Penerapan 5R (Reuse, Reduce, Recycle, Replace, Replant) dan Pengembangan Bank Sampah Pada Dusun Kembang, Desa Kembang Belor, Kecamatan Pacet Kabupaten Mojokerto Jawa Timur - Syarifudin Ahmad; Novirina Hendrasarie (UII, 2023)
Waste is one of the problems that is constantly discussed in the world as well as in Indonesia. It is necessary to make various efforts to handle waste management, both in the large scope of the country and in the community. One simple step that can be pursued is to apply 5R (reuse, reduce, recycle, replace, replant) in order to foster community enthusiasm for caring for the environment at the household level in simple waste management. In its development, there is one waste bank that is running well, namely the Sekar Tani waste bank group located in Kembang Hamlet. In practice, the waste bank has an impact on the community from an economic point of view, namely the results of the waste obtained as tax payments by its customers. However, in terms of waste management, it is considered less than optimal. In its implementation, the researchers found the results of the community's role in managing waste by using the 5R implementation in Kembang Hamlet, being able to reduce waste up to 52% of the total generation. Meanwhile, by applying the 5R principle in the community, it is able to increase the waste bank in Kembang Hamlet.